Tingkat Kemampuan Renang Gaya Bebas pada Siswa SD Kelas Atas Se-Kecamatan Puring Tahun Ajaran 2024/2025 - Puput Widodo; Nurul Latifah (Journal on Education, 2025)
The achievement obtained by upper elementary school students in Puring District was that they succeeded in passing the selection from the District Level to the Provincial Level for the sport of swimming. The aim of this research is to determine the level of freestyle swimming ability of upper class students in Puring District for the 2024/2025 academic year. This research uses a quantitative approach using a descriptive research design. The instruments in this research used survey tests and time measurement tests using a stopwatch to collect the required data in the form of tests and measurements with indicators to determine arm muscle strength, leg muscle strength and freestyle swimming speed of 25 meters. The population used in this research was upper elementary school students in Puring District for the 2024/2025 academic year. In this research, the data was analyzed descriptively with percentages. The level of freestyle swimming ability among upper grade elementary school students in Puring District showed that 6% had Very Good ability, 1% had Good ability, 1% had Fair ability, 2% had Poor ability, and 91% were in the Very Poor category.